2012
DOI: 10.1104/pp.112.198507
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Arabinogalactan Proteins from the Root Caps of Pea and Brassica napus on Aphanomyces euteiches Zoospore Chemotaxis and Germination      

Abstract: Root tips of many plant species release a number of border, or border-like, cells that are thought to play a major role in the protection of root meristem. However, little is currently known on the structure and function of the cell wall components of such root cells. Here, we investigate the sugar composition of the cell wall of the root cap in two species: pea (Pisum sativum), which makes border cells, and Brassica napus, which makes border-like cells. We find that the cell walls are highly enriched in arabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
124
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 87 publications
(125 citation statements)
references
References 81 publications
1
124
0
Order By: Relevance
“…Although we show that galactancontaining polymers such as RGI are constituents of potato root exudates, AGPs appear to be the most abundant molecules. This observation is in agreement with previous findings reporting the presence of AGPs in quite high amounts in root exudates of various plant species (Moody et al, 1988;Durand et al, 2009;Ma et al, 2010;Cannesan et al, 2012). However, AGPs were not the only HRGPs represented in the root exudates of potato.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Although we show that galactancontaining polymers such as RGI are constituents of potato root exudates, AGPs appear to be the most abundant molecules. This observation is in agreement with previous findings reporting the presence of AGPs in quite high amounts in root exudates of various plant species (Moody et al, 1988;Durand et al, 2009;Ma et al, 2010;Cannesan et al, 2012). However, AGPs were not the only HRGPs represented in the root exudates of potato.…”
Section: Discussionsupporting
confidence: 83%
“…Although less well studied, a higher defensive state seems to occur in roots compared with above-ground organs of the plants (Attard et al, 2010;Millet et al, 2010;Balmer et al, 2013). In addition, the root immune response seems to vary between different root tissues (Millet et al, 2010;Cannesan et al, 2011Cannesan et al, , 2012. Several studies have shown that root caps display enhanced local resistance to pathogen attacks compared with the elongation zone, which is often described as the primary site of infection (Gunawardena and Hawes, 2002;Gunawardena et al, 2005;Cannesan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…During their detachment from the root cap, border cells of legumes export a large number of proteins, the secretome, containing antimicrobial enzymes, including chitinase, peptidase, and glucanase (Wen et al, 2007(Wen et al, , 2009. Furthermore, pea border cells secrete other compounds such as extracellular DNA, the phytoalexin pisatin, and arabinogalactan proteins that contribute to root protection against soil-borne pathogens (Wen et al, 2009;Cannesan et al, 2011Cannesan et al, , 2012Hawes et al, 2011).…”
mentioning
confidence: 99%